Theoretical Analysis of Pancasila Student Character and Implications for Counseling Guidance - Tanjung, Romi Fajar; Nurvadila, Lativa; Azizi, Muhammad; Hanum, Mutiara Aldila; Rahmadani, Rahmadani; Ardimen, Ardimen (International Journal of Research in Counseling, 2022)
Character education is cultural wisdom from the diversity of values ??and social life to build a nation's civilization. To achieve this goal, the education system develops three subsystems, namely administration, education, and student assistance or coaching. Orientation and advice areas fall under student support or training areas. Increasing character education can be achieved through the provision of knowledge, teaching or training. Ensure the achievement of educational goals in the management of education, especially in strengthening student character education. The purpose of this article is to identify the reasons for the publication of the Pancasila student character program and to analyze the Pancasila character program and its implications for guidance and counseling services. The development of the era, especially in the field of technology, eliminates or shifts the culture and Pancasila values ??that characterize Indonesian society. The Pancasila character program aims to restore Pancasila values. Guidance and counseling services are one of the supports for the achievement of the Pancasila character program which focuses on the basic service components in achieving the six indicators of Pancasila character.